The Influence of Adsorbates on the Growth Mode of Gold Islands Electrodeposited on the Basal Plane of Graphite - Martín, H. (2000)
Gold electrodeposition on C(0001) from aqueous 0.5 mM AuCl3·HCl, in the range of apparent charge density (6 ≤ q ≤ 10 mC/cm2) and under mass transport kinetic control from the solution side, results in the formation of nanometer to micrometer size Au(111) islands. These islands consist of a small three-dimensional (3D) central core and large quasi-two-dimensional (2D) dendritic branches. Ex situ scanning tunneling microscopy (STM) imaging data show that the shape of islands is determined by anisotropic surface diffusion contributions. The addition of citric acid to the plating solution hinders branching and promotes 3D island growth. The adsorption of citric acid at step edges hinders interterrace gold atom surface diffusion, as concluded from in situ STM imaging. Conversely, the addition of an excess of sodium chloride enhances 2D island growth and dense branching formation. These results can be explained considering that the presence of adsorbates either increases or decreases the height of activation energy barriers for interterrace surface diffusion. In this way, the change of the island aspect ratio with the nature of the additive can be explained.